Persepsi Siswa SMA YATPI GODONG Tentang Pentingnya Materi Perawatan Jenazah dalam Pembelajaran Pendidikan Agama Islam - Abdul Rohmat (STIKes Ibnu Sina Ajibarang, 2026)
The subject of corpse care is one of the important competencies in Islamic Religious Education (PAI) at the senior high school level, which is obligatory (fardhu kifayah). However, the complexity of the material and the presence of psychological barriers often make students less interested or feel afraid. This study aims to analyze in-depth the perceptions of SMA YATPI Godong students regarding the importance of corpse care, the factors that influence these perceptions, and the urgency of this competency as a provision for social life. This study uses a qualitative descriptive approach supported by simple quantitative data percentages. The subjects were 35 grade XI students, selected using a purposive sampling technique. Data collection was carried out through participant observation, questionnaire distribution, in-depth interviews, and documentation. Data analysis followed an interactive model that includes data condensation, data presentation, and drawing conclusions. The results showed that the majority of students (82.8%) had a very positive perception of the urgency of this material and were aware of its socio-cultural responsibility. The main factors influencing students' perceptions included the demonstration method using mannequins implemented by teachers, internal religiosity values, and the encouragement of societal expectations. These skills are considered essential not only for fulfilling academic obligations but also as a form of student readiness to engage and contribute significantly to their social environment in the event of grief.